Contributions of Sokoto Caliphate in Educating the Public and the Lessons for today - Aliyu Umar Sharu; Safina Musa Bodinga (Al-Amīr Research Journal for Islamic Studies, 2025)
The Sokoto Caliphate's educational system, established in the 19th century, made significant contributions to promoting Islamic sciences, literacy, and skills development. The system was characterized by a holistic approach to education, diverse teaching methods, and an emphasis on inclusivity and equity. This study explores the features and challenges of the Sokoto Caliphate's educational system and highlights its lessons for contemporary education, particularly in developing areas of the world. By examining the system's strengths and weaknesses, this research provides insights into the enduring impact of the Sokoto Caliphate's educational legacy and its relevance to modern educational challenges. Keywords: Sokoto Caliphate, education, curriculum, Usmanu Danfodiyo, Islam, Hausaland, women’s right